A case of CD20 positive peripheral T-cell lymphoma: not otherwise specified masquerading as botryomycosis - Potlapati, Amruthavalli; George, Neethu Mary; Gangaiah, Narendra; Thimmappa, Veena (International Journal of Research in Dermatology, 2019)
Peripheral T-cell lymphoma (PTCL), a type of non-Hodgkin’s lymphoma, is an uncommon malignancy frequently involving the skin either as primary or secondary manifestation of the disease. Lymphomas may occasionally masquerade as infectious diseases especially when it is not associated with significant lymphadenopathy. Botryomycosis is a chronic granulomatous suppurative bacterial infection, predominantly caused by Staphylococcus aureus, which is seen on trauma prone sites. Herein we present a case of a 33 years old male who presented to us with multiple rapidly growing friable masses on the chest wall of six weeks duration which clinically pointed towards botryomycosis. Lack of response to treatment with intravenous antibiotics and absence of grains and granuloma in the biopsy specimen made us further proceed for immune-histochemical evaluation which confirmed a rare type of CD20 positive PTCL. In conclusion, our case alerts physician to maintain a high index of suspicion for unusual entities in cases they encounter, cases with unusual presentation or atypical response to treatment.